APPOINTMENT AND DISCLAIMER OF VILLAGE EQUIPMENT BASED ON LEGISLATION IN INDONESIA: PENGANGKATAN DAN PEMBERHENTIAN PERANGKAT DESA BERDASARKAN PERATURANN PERUNDANG-UNDANGAN DI INDONESIA - Muchlis Sadzili; Siti Khoiriah; Yhannu Setyawan (Constitutional Law Society, 2022)
This study aims to find out the problems that occur related to the appointment and dismissal of village officials, provide suggestions regarding problems in South Sukadana Village and Bumi Nabung Village, and find solutions to differences in norms related to the laws and regulations governing the appointment and dismissal of village officials. This research is a legal research using a normative writing method using a statutory approach and empirically using a direct field investigation approach by conducting interviews with the South Sukadana Village Head, Bumi Nabung Village Head and Sukadana Sub-District Head. Based on the results of the study, there was an expansion of norms which then caused problems in each village in terms of recommendations issued by the sub-district head. The problem dragged on and there was a temporary stagnation of the wheels of government in South Sukadana Village and Bumi Nabung Village.